Clinical and Sociodemographic Characteristics of Recently Identified Leprosy Patients in Sangli District of Maharashtra - Chandrahas Kurane, Swati; Dani, Pravin (Journal of Neonatal Surgery, 2025)
Exploring the prevalence of physical disabilities due to leprosy disease is a crucial work as it is a major sequela leading to loss of earnings, social stigma and psychological strain. This study has been carried out to evaluate the sociodemographic profile, clinical features pertaining to disabilities due to leprosy among newly detected leprosy cases in Sangli district of Maharashtra. It is a descriptive cross-sectional study carried out at tertiary health centre from 8 February 2024 to 31 December 2024. Newly detected leprosy patients from all community health centres and leprosy care centres at Sangli District were included in the study after taking informed consent. A structured questionnaire was used to get information about sociodemographic profile, clinical features, disability and treatment status. The data was procured from the National Leprosy Elimination Programme (NLEP) registry with the permission of appropriate authorities. The community level interview was also conducted to get the complete information. Demographic, socio-economic details were noted down. Detail clinical features like duration of illness, type and subtype of leprosy, type of deformities, the WHO grading and EHF scores were noted. Presence of lepra reaction and its type was documented. Non-compliance for the treatment and its reason were also recorded. Total 55 patients were enrolled for the study. Patients were classified as per WHO grading system into Grade 0, Grade 1 and Grade 2 categories. The number of multibacillary cases were alarming; suggests the changing disease pattern, latent disease in the community and delayed presentation.